PENGARUH TRADISI JAWA DALAM PENDIDIKAN ISLAM: (The Influence of Javanese Tradition on Islamic Education) - Syayidati Rohmah Fitriani (Raqib: Jurnal Studi Islam, 2025)
Tradition is a community's custom passed down from generation to generation from its ancestors. Within tradition, several ancestral values are conveyed through the procedures for carrying out a tradition, such as Javanese tradition, which is rich in values that can be implemented in education. Javanese tradition is not only rich in social and cultural values but also rich in spiritual values such as worship, gratitude, almsgiving, and others. These values can be applied in an Islamic educational approach, so that character building can be carried out in a varied and enjoyable way. By introducing character through Javanese tradition, students are not only able to interact with each other but can also train their faith and devotion to their creator. Therefore, Javanese tradition can help students understand Islamic teachings, just as the Walisongo used their approach to preaching through traditions in the surrounding area. But the guardians were not careless in using these traditions, they actually carried out cultural and Islamic acculturation by removing elements in traditions that were not in accordance with Islamic teachings so that their preaching could be well received by the surrounding community until large-scale Islamization occurred in Java. For this reason, educators must also be careful and clever in choosing Javanese traditions that are in accordance with Islamic teachings because there are quite a few Javanese traditions that still deviate from Islamic teachings so that the character instilled is in accordance with Islamic law that has been taught to us as human beings.